The Effectiveness of Group Social Work Intervention With Developmental Approach on Psychosocial Empowerment of Female-Headed Households - Elham Torabi Momen; Ghoncheh Raheb; Fardin Ali Pour; Akbar Biglarian (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective Female-headed households are one of the minority groups of women in Iran and other countries, grappling with many problems. This group normally face with too many obstacles in their personal, family and social life. So much difficult tasks assigned to these women, put unbearable pressure and tensions on them, and gradually makes them susceptible to a variety of mental disorders. Considering the wide range of issues, problems, limitations and vulnerability of female-headed households and their being as one of the target groups of social workers; it is important to provide professional services by social workers with the aim of psychosocial empowerment of this group. Thus the present study aimed to investigate the effectiveness of group social work intervention with developmental approach on psychosocial empowerment of female-headed households. Materials & Methods This research was quasi-experimental with pretest/posttest design and control group. The study population consisted all female-headed households living in Tehran. The sample of women heads of households were randomly chosen from the Guide Institute of Imam Ali (AS). The inclusion criteria were the ability to read and write, aged 20 to 45 years, and willingness to participate in the study. Finally, a total of 60 women heads of households were selected and randomly divided into two intervention and control groups. Group social work intervention with developmental approach was taught in eight 90-minute sessions to the experimental group. The control group did not receive intervention. In order to assess the psychosocial empowerment of women heads of household before the first session and after the last session, social demographic data and psychological empowerment questionnaire were distributed among the participants and were filled by them. In this study, questionnaires on demographic information and Moradi (2010) sociopsychological empowerment questionnaire were used. Construct validity and reliability of the questionnaires have been approved. Also the validity and reliability of the questionnaire was assessed by the investigator again. The Cronbach α of the questionnaire was equal to 0.79. The content and face validity of the questionnaire were confirmed by the University of Welfare and Rehabilitation Sciences. The data were analyzed by SPSS 22. The analyses were performed by descriptive statistics such as mean, frequency, standard deviation and inferential statistics, including Levine, KS, paired t test, and covariance. Results The results showed a significant difference between psychological empowerment of women headed households, before and after the intervention. This significant difference was observed in the scales of psychological empowerment, including self-esteem, self-efficacy, intellectual independence and sense of power (P<0.001) and subscales of social empowerment, including participation in social activities and pluralism (P<0.001). Also there were significant differences (P<0.001) between trained and untrained people in psychological empowerment with the scales of self-esteem, self-efficacy, intellectual independence, sense of power and in social empowerment with the scales of participation in social activities and pluralism. Conclusion According to the study results, group social work intervention sessions with psychosocial developmental approach to empowering female-headed households is effective. The wider use of this type of intervention by professionals can empower and improve the lives of this group of people.